Exploration of chiral diastereomeric spiroketal (SPIROL)-based phosphinite ligands in asymmetric hydrogenation of heterocycles. Issue 60 (24th June 2020) - Sun, Siyuan; Nagorny, Pavel
Abstract : New and readily available chiral SPIROL-based diphosphinite ligands (SPIRAPO) have been prepared and employed for iridium catalyzed asymmetric hydrogenations of quinolines, quinoxalines and 2 H -1, 4-bezoxazin-2-ones. Abstract : New and readily available chiral SPIROL-based diphosphinite ligands (SPIRAPO) have been prepared and employed for iridium-catalyzed asymmetric hydrogenations of quinolines, quinoxalines and 2 H -1, 4-bezoxazin-2-ones. While the structurally similar ( R, R, R )-SPIRAPO and ( R )-SPINOL-based phosphinites were not the best ligands for these transformations, the ( S, R, R )-diastereomer of SPIRAPO was found to be highly effective ligand for the reduction of 20 different heterocyclic systems with loadings as low as S/C = 10 000. This dearomatizative hydrogenation provided direct access to optically active tetrahydroquinolines in high enantioselectivities (up to 94% ee) and excellent yields (up to 99%), and was used to generate 1.75 g of natural alkaloid (−)-( R )-angustureine. This protocol was subsequently extended to achieve asymmetric hydrogenation of quinoxalines and 2 H -1, 4-benzoxazin-2-ones in good to excellent enantioselectivities.